2020
DOI: 10.1101/2020.03.27.006403
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking bacterial lineages in complex and dynamic environments with applications to growth control and persistence

Abstract: As microbes deplete local resources and transition from exponential to stationary phase they can change greatly in size, morphology, growth and expression-profiles. These responses can also vary importantly between individual cells, as shown by population snapshots. However, it has been difficult to track individual cells along the growth curve to determine the progression of events or correlations between how cells enter and exit dormancy. We have developed a platform for tracking >10 5 parallel cell lineages… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…S5 and Movie S17). Since it is reported that the time to regrowth of dormant cells after drug removal is heterogeneous among dormant cells [23], it is plausible that these cells would eventually regrow after long lags. However, these late regrowers cannot significantly contribute to the regrowing cell populations due to the exponential penalties from the delay of regrowth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…S5 and Movie S17). Since it is reported that the time to regrowth of dormant cells after drug removal is heterogeneous among dormant cells [23], it is plausible that these cells would eventually regrow after long lags. However, these late regrowers cannot significantly contribute to the regrowing cell populations due to the exponential penalties from the delay of regrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is plausible that these cells would eventually regrow as persisters with long lags. In fact, it has been shown by the single-cell measurements with a mother machine microfluidic device that the time to regrowth after drug removal is heterogeneous among dormant cells [23]. It should be noted that these late regrowers are detectable in the killing curve assay but not in the single-cell measurements with the MCMA microfluidic device due to the overgrowth of the early regrowers.…”
Section: Stationary Phase Environments Increase the Frequencies Of Dormant Persistersmentioning
confidence: 97%
See 2 more Smart Citations
“…Experiment schematic. Cells were recovered in the mother machine using glucose medium, and then connected to a flask with culture growing in the same medium 28 . Media switch was performed the same way as for the batch cultures, and the flow was then restarted towards the mother machine.…”
Section: Extended Datamentioning
confidence: 99%